Oral structure & biology - Radlanski, Ralf J. ([S.l.] : Quintessence Publishing Co, Inc., 2019)
Knowledge of the structures of the orofacial region from the macroscopic scale to the molecular level and pathologic changes to those structures enables practitioners to successfully treat patients or seek treatment options. This book presents the structural biologic foundations underpinning dental and oral medicine. Beginning with an overview of the anatomy of the mouth and moving on to the evolution of the oral structures and pre- and postnatal development of the oral cavity, related facial structures, and the teeth, this book describes each part of the orofacial region in terms of its morphology, tissue structure, cellular properties, and development.
Oral structure & biology -- Contents -- Preface -- Chapter 1. Definitions, Objectives, and Clinical Relevance -- Chapter 2. The Mouth and Its Parts -- Chapter 3. Evolution -- Chapter 4. Morphogenesis -- Chapter 5. Development of the Oral Cavity in Relation to Facial Development -- Chapter 6. Tooth Development -- Chapter 7. Dental Enamel -- Chapter 8. Dentin -- Chapter 9.Pulp and Root -- Chapter 10. Periodontium -- Chapter 11. Cementum -- Chapter 12. Periodontal Ligament -- Chapter 13. Alveolar Bone and Jawbone -- Chapter 14. Oral Mucosa -- Chapter 15. Salivary Glands -- Chapter 16. Immune System -- Chapter 17. Development of the Dentition and Teeth Eruption -- Chapter 18. Temporomandibular Joint -- Index.
Includes bibliographical references and index.
Keywords: Stomatognathic System -- embryology; Stomatognathic System -- growth & development